Barriers to Accessing Primary Care and Appropriateness of Healthcare Among Immigrants in Italy - Di Napoli, Anteo; Ventura, Martina; Spadea, Teresa; Giorgi Rossi, Paolo; Bartolini, Letizia; Battisti, Laura; Cacciani, Laura; Caranci, Nicola; Cernigliaro, Achille; De Giorgi, Marcello; Fanolla, Antonio; Lazzeretti, Marco; et al. (Frontiers in Public Health, 2022)
Introduction: The health status and health care needs of immigrant populations must be assessed. The aim of this study was to evaluate barriers to accessing primary care and the appropriateness of health care among resident immigrants in Italy, using indicators regarding maternal health, avoidable hospitalization, and emergency care. Methods: Cross-sectional study using some indicators of the National Monitoring System of Health Status and Healthcare of the Immigrant Population (MSHIP), coordinated by the National Institute for Health, Migration and Poverty (INMP), calculated on perinatal care, hospital discharge, and emergency department databases for the years 2016-2017 in nine Italian regions (Piedmont, Trento, Bolzano, Emilia-Romagna, Tuscany, Umbria, Latium, Basilicata, Sicily). The analyses were conducted comparing immigrant and Italian residents. Results: Compared to Italian women, immigrant women had fewer than five gynecological examinations (8.5% vs 16.3%), fewer first examinations after the 12th week of gestational age (3.8% vs 12.5%), and fewer than two ultrasounds (1.0% vs 3.8%). Compared to Italians, immigrants had higher standardized rates (x 1000 residents) of avoidable hospitalizations (males: 2.1 vs 1.4; females: 0.9 vs 0.7) and of access to emergency departments for non-urgent conditions (males: 62.0 vs 32.7; females: 52.9 vs 31.4). Conclusions: In Italy, there appear to be major issues regarding accessing services and care for the immigrant population. Policies aimed at improving socioeconomic conditions and promoting integration can promote healthy lifestyles and appropriate access to health care, counteracting the emergence of health inequities in the immigrant population.